Case Report: Dupilumab combined with allergen-specific immunotherapy in severe atopic dermatitis and asthma - Tussupbekova, Galiya; Tashenov, Dauren; Syzdykova, Aigul; Davletova, Botagoz (Frontiers in Allergy, 2025)
We report a case of a 24-year-old man with long-standing, severe atopic dermatitis and partly controlled moderate bronchial asthma, marked type-2 inflammation and high molecular sensitization to house-dust mite and Alternaria allergens. Because the patient's disease was refractory to conventional topical and systemic therapies, we initiated dupilumab (600 mg SC loading dose, then 300 mg every 2 weeks) to rapidly suppress systemic T2 inflammation; subcutaneous allergen-specific immunotherapy (house-dust-mite and Alternaria, Clustek®) was started at week 8. Clinical scores and lung function were followed longitudinally, and serial biomarkers (total IgE, peripheral eosinophils, allergen-specific IgG4) were measured. The patient experienced notable clinical improvement in skin and respiratory symptoms by week 6, permitting stepwise reduction of inhaled therapy; a progressive rise in allergen-specific IgG4 was observed after AIT. At week 48 the patient achieved sustained clinical remission (SCORAD 1; DLQI 0; ACQ-5 0) with normalized eosinophils and reduced total IgE. While a single case cannot prove causality or isolate the independent effect of AIT from dupilumab, this well-documented example demonstrates the feasibility and tolerability of initiating dupilumab followed by targeted AIT and suggests complementary clinical and serologic dynamics consistent with early T2 suppression and later tolerance induction. These observations support further systematic evaluation of combined biologic + AIT strategies to determine their disease-modifying potential and optimal sequencing.